APLIKASI KAYU SECANG (Caesalpinia sappan L.) DALAM UPAYA PREVENSI KERUSAKAN DNA AKIBAT PAPARAN ZAT POTENSIAL KARSINOGENIK MELALUI MNPCE ASSAY - Sugiyanto, Raisatun Nisa; Putri, Shofy Rahmadani; Damanik, Ferina Septiani; Sasmita, Gusti Made Aryandana (Program Kreativitas Mahasiswa - Penelitian, 2013)
Genotoxic effect is related to the mutation of the gene in the DNA. Caesalpinia sappan L. is one of Caesalpiniaceae family found in Indonesia containing brazilin and brazilein. It has been reported to have antioxidant activity and could potentially be used in the prevention of DNA damage. The aim of this study is to know the activity of Caesalpinia sappan L. ethanolic extract (CEE) as antigenotoxic agent. Caesalpinia sappan L. heartwood was macerated with 70% ethanol. The antigenotoxic activity was observed by micronucleus assay in vivo modeled by cyclophosphamide-induced female Swiss mice. CEE treatment was done with the dosage of 250, 500, and 1000 mg/kgBW. Mice peripheral blood was taken in the end of the study and observed for the number of mononuclear polychromatic erythrosite (MNPCE) by Giemsa staining. Molecular docking was done to evaluate the affinity of brazilin, brazilein, and cyclophosphamide to CYP 3A4 enzyme. Based on the study, CEE has antigenotoxic activity showed by the number of MNPCE which is reduced significantly compared to cyclophosphamide control group. The mechanism of antigenotoxic activity is probably because of the inhibition of cyclophosphamide binding to CYP 3A4 enzyme by brazilin and brazilein, as the affinity to CYP 3A4 of brazilin and brazilein were higher than cyclophosphamide.            Keyword: Antigenotoxic, MNPCE Assay, Caesalpinia sappan L.